2021
DOI: 10.17275/per.21.82.8.4
|View full text |Cite
|
Sign up to set email alerts
|

Social Information Processing in Preschool Children: Relations to Social Interaction

Abstract: The Social Information Processing Process Model consists of organizing the social adaptation and behavior of children in line with their responses to the social situations they encounter with their peers in their daily lives. The Social Information Processing Model affects children's ability to interact with their peers, their level of interaction, and provides information about the structure of interaction. In this direction, it was aimed to examine the relationship between social information processing and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Torres and coauthors (2016) found that deaf adolescents and adults had lower scores than hearing participants in all social information processing steps based on Crick and Dodge's (1994) SIP model (coding, interpretation, goal formulation, response generation, response decision, and representation). Senol and Metin's (2021) study indicated that there is a positive relationship between social information processing and social interaction. Children's social interactions affect their behaviors and responses to the situations they experience (Kington, 2013;Henrich et al, 2001;Keller et al, 2004).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Torres and coauthors (2016) found that deaf adolescents and adults had lower scores than hearing participants in all social information processing steps based on Crick and Dodge's (1994) SIP model (coding, interpretation, goal formulation, response generation, response decision, and representation). Senol and Metin's (2021) study indicated that there is a positive relationship between social information processing and social interaction. Children's social interactions affect their behaviors and responses to the situations they experience (Kington, 2013;Henrich et al, 2001;Keller et al, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…The Social Information Processing Model consists of social and behavioral adaptation of children in line with their responses to the social situations they encounter. This can be understood as children who make positive comments in social situations, who create and react positively, are more cooperative in the context of social interaction (Senol & Metin, 2021). Social awareness is defined as understanding ethical behavior, empathizing with others, and recognizing social support and systems (Alexander & Vermette, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…According to Windaniati (2015), the process of self-adjustment or adaptation is a natural and dynamic thing that aims to change individual behavior so that there is a relationship that is more in line with environmental conditions. while the decrease in the level of intellectual communication can be influenced by the availability of self-social information processes and adaptation of student behavior (Şenol & Metin, 2021). The 4 th indicator, namely providing help to others, and the 8 th indicator, namely choosing to live in groups, have the lowest average score with a score of 2.42.…”
Section: Social Interactionsmentioning
confidence: 99%